Comparison of the psychological evaluation test and classical psychoanalysis in infertile women - Franco, J. G.; Silva, P. G.; Ache, R. S.; Baruffi, R. R.; Mauri, A. L.; Petersen, C. G.; Felipe, V; Vagnini, L.; Oliveira, J. (Reproductive Healthcare Ltd, 2004)
This study aims to compare a psychological evaluation test to classical psychoanalysis in infertile women. Two hundred women were submitted to the Psychological Evaluation Test (PET). The sum of the scores for the responses ranged from 15 to 60 points, with scores 30 points being defined as 'psycho-emotional maladjustment' (cut-off point: median + 25%). For comparison, the patients were simultaneously submitted to a psychological examination by a psychologist, who was unaware of the PET results. of the 200 patients, 66 (33%) presented a test with greater than or equal to30 points ('psycho-emotional maladjustment') and 134 (67%) a test with <30 points (normal). Upon psychological examination, 105 (52.5%) presented an abnormal evaluation and 95 (47.5%) a normal evaluation. For the PET, statistical analysis showed 82% efficiency, 62% sensitivity, 98% positive predictive value, 99% specificity, 70% negative predictive value, likelihood ratio for a positive test result 62, and likelihood ratio for negative test result 0.38. The PET proved to be a useful clinical instrument, being of help in the selection of patients with psychological needs induced by infertility.
Keywords: infertility; psychological evaluation; psychological test; score